2016
DOI: 10.1089/neu.2015.4251
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effects of Concussion on Electrophysiological Indices of Attention in Varsity College Athletes: An Event-Related Potential and Standardized Low-Resolution Brain Electromagnetic Tomography Approach

Abstract: This study investigated the effects of a past concussion on electrophysiological indices of attention in college athletes. Forty-four varsity football athletes (22 with at least one past concussion) participated in three neuropsychological tests and a two-tone auditory oddball task while undergoing high-density event-related potential (ERP) recording. Athletes previously diagnosed with a concussion experienced their most recent injury approximately 4 years before testing. Previously concussed and control athle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(63 citation statements)
references
References 79 publications
4
57
2
Order By: Relevance
“…According to a model proposed by Molfese (2015), neural networks reorganize after concussion by developing new local and distal networks to compensate for reductions of efficiency caused by brain damage. Ledwidge and Molfese (2016) provided evidence that concussed athletes generate atypical brain patterns by recruiting additional neuronal resources relative to controls in such a way that allows concussed athletes to achieve similar performance levels (McAllister, et al, 2001;McDonald, Saykin, & McAllister, 2012;Ozen, Itier, Preston, & Fernandes, 2013). When applied to current study findings, the recruitment of additional brain resources that may have taken place over several months postconcussion could explain normal behavioral performance levels in multi-concussed athletes.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…According to a model proposed by Molfese (2015), neural networks reorganize after concussion by developing new local and distal networks to compensate for reductions of efficiency caused by brain damage. Ledwidge and Molfese (2016) provided evidence that concussed athletes generate atypical brain patterns by recruiting additional neuronal resources relative to controls in such a way that allows concussed athletes to achieve similar performance levels (McAllister, et al, 2001;McDonald, Saykin, & McAllister, 2012;Ozen, Itier, Preston, & Fernandes, 2013). When applied to current study findings, the recruitment of additional brain resources that may have taken place over several months postconcussion could explain normal behavioral performance levels in multi-concussed athletes.…”
Section: Discussionmentioning
confidence: 60%
“…For instance, event-related potential (ERP) studies revealed significant and persistent N1 (Gosselin, Theriault, Leclerc, Montplaisir, & Lassonde, 2006), N2 (Ledwidge & Molfese, 2016), P2 (Gosselin, et al, 2006), P3 (De Beaumont, Brisson, Lassonde, & Jolicoeur, 2007;Gaetz, Goodman, & Weinberg, 2000;Gosselin, et al, 2006;Ledwidge & Molfese, 2016;Theriault, De Beaumont, Gosselin, Filipinni, & Lassonde, 2009) waveform components alterations when concussed athletes performed cognitive tasks relying on attentional processes in the acute phase as well as several years post-accident relative to controls. ERPs are computed from the averaged EEG signal time-locked to an event of interest, often the presentation of a stimulus.…”
Section: Introductionmentioning
confidence: 99%
“…The SRC-ERP literature has primarily examined changes in two cognitive-evoked ERP components, the N200 and P300 (see Brush and colleagues [40] for review). This research indicates that the amplitude and latency of the P300, reflecting context-updating and resource allocation [41,42], are altered following SRC during selective attention [43][44][45] and working memory [46,47]. The effects of SRC on the N200, indexing mismatch/novelty detection, cognitive control, and/or response monitoring depending on task demands [48], are less clear than the P300.…”
Section: Effects Of Src On Cognitive-evoked Erpsmentioning
confidence: 84%
“…The effects of SRC on the N200, indexing mismatch/novelty detection, cognitive control, and/or response monitoring depending on task demands [48], are less clear than the P300. Some report altered N200 amplitudes [43,44,49] and latencies [49,50] associated with a history of concussion, whereas others failed to find differences in amplitude [46,50] or latency [43]. Importantly, these altered ERP correlates often occur despite normative performance on behavioral neuropsychological assessments [43,44,46].…”
Section: Effects Of Src On Cognitive-evoked Erpsmentioning
confidence: 99%
See 1 more Smart Citation